Association between hypothyroidism and metabolic profile in gestational diabetes mellitus - Pinto, Sara; Nachtergaele, Charlotte; Croce, Laura; Carbillon, Lionel; Benbara, Amélie; Fabre, Emmanuelle; Rotondi, Mario; Cosson, Emmanuel (Frontiers in Endocrinology, 2025)
IntroductionThyroid hormones exert many effects on glucose metabolism. Gestational diabetes mellitus (GDM) and hypothyroidism during gestation (HG) are the most common gestational endocrinopathies and seem to be associated. We therefore explored in women with GDM whether the presence of HG is associated with a different metabolic profile.Materials and methodsWe included 1,290 pregnant women with GDM [International Association of the Diabetes and Pregnancy Study Group (IADPSG)/World Health Organization (WHO) criteria] and no history of hypothyroidism prior to pregnancy who had a measure of thyroid-stimulating hormone (TSH) and anti-thyroperoxidase antibodies during their hospital stay after GDM diagnosis. Patients with thyrotoxicosis and previous bariatric surgery were excluded. We evaluated concomitant blood pressure, fasting glycemia, insulinemia [with calculation of homeostatic model assessment for insulin resistance (HOMA-IR) index], glycated hemoglobin (HbA1c), and lipid profile according to the presence of HG (American Thyroid Association 2017 definition: TSH ≥ 4 mUI/L).ResultsThe mean (± standard deviation) age was 33 ± 5 years, the mean body mass index was 27 ± 5 kg/m2, and 117 women (9%) displayed HG. HG was associated with higher HbA1c (5.35 ± 0.56% vs. 5.22 ± 0.52%, p = 0.009), even after adjustment for gestational age, age, and body mass index. TSH was also positively associated with HbA1c (p = 0.006) and HOMA-IR (p = 0.002). Patients with HG displayed less often an early GDM, with their fasting glycemia before 24 weeks of amenorrhea being lower than that of patients with a TSH < 4 mU/L.ConclusionIn our cohort of patients with GDM, women with HG showed higher HbA1c than those without and HOMA-IR was positively associated with the level of TSH.